(3GdYbhO GdJLGQjI (B/s - (3Wg, eUWai ceGds ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2005)
(3GdGMcGe GdYGeI ddHjY GdJLGQj eY HYV CfhGY GdHjhY GdJLGQjI h GdQgf GdJLGQj GdYGOj h GdQgf Ohf GfJbGd GdMjGRI GVGaI Gdi JfXje GdeSJhOYGJ GdYGeI h GdUchc GdJj jUOQgG GdeSJhOY GdYGe h GdGMcGe GdYGeI ddhcGdI GdJLGQjI h GdhcGdI HGdYehdI hhcGdI GdYbhO(B, (3cPdc JYRjR YbO Gdfbd h NUGFUg h YbO fbd GdHVGFY h cPG YbO fbd GdQcGH h JYQja YbO fbd GdJcfhdhLjGJ h Jchjfg h aj GdGNjQ BKGQ GdYbO(B.s
(3eQGLY U(B.241s
Keywords: (3GdYbhOs; (3GdYbhO GdJLGQjIs